Evaluating Completeness of Reporting in Behavioral Interventions Pilot Trials: A Systematic Survey. (July 2018) - Bhatt, Meha; Zielinski, Laura; Sanger, Nitika; Shams, Ieta; Luo, Candice; Bantoto, Bianca; Shahid, Hamnah; Li, Guowei; Abbade, Luciana P. F.; Nwosu, Ikunna; Jin, Yanling; Wang, Mei; et al.
Purpose: This systematic survey evaluates the completeness of reporting in pilot and feasibility randomized controlled trials investigating behavioral interventions based on the Consolidated Standards of Reporting Trials (CONSORT) extension for pilot trials. Methods: The authors searched Medline/Pubmed and randomly selected 100 articles from 2012 through 2016 to determine the proportion of reported CONSORT extension items. They examined study factors related to reporting, including year and country of publication, psychotherapy intervention, multiple centers, industry funding, and journal endorsement of CONSORT. Results: The authors found that the mean reporting score on the CONSORT extension was 51.6% ( SD = 15.1). Studies of psychotherapy interventions had significantly higher reporting scores than other interventions (incidence rate ratio = 1.10, 95% confidence interval: 1.01–1.20). Conclusions: Our findings indicate that current reporting quality is suboptimal. Many included trials failed to provide rationale for piloting, assess feasibility objectives, or indicate clear progression to a future large trial. Reporting quality should be reevaluated following uptake of the 2016 CONSORT extension for pilot trials.